2015
DOI: 10.1002/acr.22603
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Air Pollutants and Disease Activity in Juvenile‐Onset Systemic Lupus Erythematosus Patients

Abstract: Objective. To investigate the association between exposure to air pollutants in the Sao Paulo metropolitan area and disease activity in juvenile-onset systemic lupus erythematosus (SLE) patients. Methods. A longitudinal panel study based on 409 consecutive visits of juvenile-onset SLE patients living in the Sao Paulo metropolitan area was carried out. Disease activity was evaluated in accordance with the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K), and the patients were divided into 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 18 publications
1
40
0
6
Order By: Relevance
“…Other acute effects of air pollution have also been demonstrated in some panel studies, notably on glucose metabolism [47,48] and inflammation [49]. However, we are confident that we have covered the most important endpoints, including respiratory [50] and cardiovascular [51][52][53][54] effects.…”
Section: Discussionmentioning
confidence: 72%
“…Other acute effects of air pollution have also been demonstrated in some panel studies, notably on glucose metabolism [47,48] and inflammation [49]. However, we are confident that we have covered the most important endpoints, including respiratory [50] and cardiovascular [51][52][53][54] effects.…”
Section: Discussionmentioning
confidence: 72%
“…Recent data have suggested that these types of exposure may be important triggers for systemic inflammation in SLE. Fernandes et al [9], in a study carried out in the city of São Paulo, Brazil, found an increase in the disease activity of juvenile systemic lupus erythematosus, associated with increased concentration of particulate matter 12-15 days before manifestation of disease activity. Exposure to concentrations of fine particulate matter, which are sometimes considered to be unhealthy, may lead to increased levels of some serum inflammatory markers.…”
Section: Introductionmentioning
confidence: 97%
“…Exposure to concentrations of fine particulate matter, which are sometimes considered to be unhealthy, may lead to increased levels of some serum inflammatory markers. In addition to SLE, these markers are indicative of other pathologies [9][10][11]. For example, Makar et al [11], while evaluating air pollutants and respiratory diseases, found that increased long-term exposure to PM 2.5 from levels below 8 µ/m 3 to levels above 8 µ/m 3 led to a 15% increase in the hospitalization rate for such diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Não existe, até o momento, nenhum estudo avaliando os efeitos da exposição à poluição atmosférica sobre marcadores inflamatórios em CAE de pacientes portadores de doença inflamatória sistêmica crônica, como o lúpus.Estes aspectos foram recentemente reforçados numa revisão sobre o tema pelo nosso grupo, enfatizando estudos com poluentes inaláveis de acordo com níveis de evidência 62. Existem apenas seis estudos que avaliaram os efeitos da exposição à poluição do ar sobre LES 57,58,60,61,63,64. Na última década, nosso grupo tem avaliado os efeitos deletérios da exposição à poluição atmosférica em crianças e adolescentes portadores de LESJ 60.…”
unclassified
“…61,64 Em estudo inicial, foi avaliada a influência da exposição à poluição do ar da cidade de São Paulo sobre o número de internações diárias por agudização de sete doenças reumatológicas pediátricas, incluindo LESJ e foi observada associação entre o aumento de uma variação interquartil na concentração diária de SO2 e o aumento no número de internações hospitalares devido à exacerbação das doenças estudadas após 14 dias da exposição. 60Em outro estudo retrospectivo foi encontrada associação entre a exposição à poluentes atmosféricos da região metropolitana de São Paulo (PM10, NO2 e CO) e risco aumentado de atividade moderada/grave do LESJ (SLEDAI-2K >8) após 12-15 dias da exposição 61. da cidade de São Paulo (RMSP).…”
unclassified